Copeptin: a novel prognostic biomarker in trauma: a review article - Artin Sarkarinejad; Shahram Paydar; Arezou Khosrojerdi; Maryam Hosseini (BMC, 2023)
Abstract Background Trauma has a significant impact on the overall health of individuals worldwide, being a leading cause of morbidity and mortality with long-lasting effects. The identification of suitable biomarkers is crucial to predict patient outcomes, providing information about the severity of a condition or the probability of a specific outcome. Hence, in this study, we addressed a new biomarker, copeptin, and discussed its prognostic roles in various trauma researches. Main body Copeptin is a peptide derived from the precursor of the hormone vasopressin, which is released in response to stress. Copeptin can serve as a valuable biomarker for determining the severity, prognosis, and outcome of trauma patients. Elevated levels of copeptin are associated with increased mortality and poor clinical outcomes in patients with severe injuries or bleeding. Implementing copeptin measurements in clinical practice can enable healthcare providers to more accurately gauge the degree of trauma and predict patient mortality and morbidity outcomes facilitating prompt interventions and personalized treatment. Conclusion The measurement of novel biomarker copeptin can serve as a prognostic molecule for further outcomes in trauma patients. Nevertheless, supplementary research is needed to fully comprehend its role in the development and progression of traumatic injuries.